2015
DOI: 10.1001/jama.2015.7916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Doses of a Monovalent H7N9 Influenza Vaccine With and Without AS03 and MF59 Adjuvants on Immune Response

Abstract: IMPORTANCE Human infections with the avian influenza A(H7N9) virus were first reported in China in 2013 and continue to occur. Hemagglutinin H7 administered alone is a poor immunogen necessitating evaluation of adjuvanted H7N9 vaccines.OBJECTIVE To evaluate the immunogenicity and safety of an inactivated H7N9 vaccine with and without AS03 adjuvant, as well as mixed vaccine schedules that included sequential administration of AS03-and MF59-containing formulations and of adjuvanted and unadjuvanted formulations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
94
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 24 publications
3
94
2
3
Order By: Relevance
“…Several H7 inactivated influenza vaccines and live-attenuated influenza vaccines are in clinical development, but have not been highly immunogenic in humans [810]. Adjuvanted vaccines have shown improved immunogenicity [1114]. A recent mix-and-match study demonstrated that a monovalent H7N9 vaccine adjuvanted with AS03 induced a better immune response than the nonadjuvanted or MF59-adjuvanted formulations, when administered to adults according to a 2-dose schedule [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several H7 inactivated influenza vaccines and live-attenuated influenza vaccines are in clinical development, but have not been highly immunogenic in humans [810]. Adjuvanted vaccines have shown improved immunogenicity [1114]. A recent mix-and-match study demonstrated that a monovalent H7N9 vaccine adjuvanted with AS03 induced a better immune response than the nonadjuvanted or MF59-adjuvanted formulations, when administered to adults according to a 2-dose schedule [14].…”
mentioning
confidence: 99%
“…Adjuvanted vaccines have shown improved immunogenicity [1114]. A recent mix-and-match study demonstrated that a monovalent H7N9 vaccine adjuvanted with AS03 induced a better immune response than the nonadjuvanted or MF59-adjuvanted formulations, when administered to adults according to a 2-dose schedule [14]. Here, we present the findings of a study that evaluated H7N9 vaccine formulations with hemagglutinin (HA) antigen doses of 2.78 and 5.09 µg, given with AS03 adjuvants of different potency and a nonadjuvanted formulation.…”
mentioning
confidence: 99%
“…7 There are 2 main lines of evidence indicating that the respiratory tract of ferrets closely resembles that of humans; first, ferrets possess a predominance of a-(2-6)-linked sialic acids on the upper airway epithelia and second, avian H5N1 and human H3N2 influenza viruses exhibit similar patterns of virus attachment to tissues from both species. [8][9][10][11][12] The primary goal of the ferret studies described below was to evaluate the antigen sparing capacity of the adjuvant; in this regard and consistent with clinical study designs addressing the same question, 13 the most efficient use of animals called for an experimental design with a high dose antigen alone group compared to lower dose antigen groups with or without adjuvant.…”
Section: Resultsmentioning
confidence: 99%
“…H5N1 and H7N9 vaccines have proven to be poorly immunogenic in these trials, often requiring multiple doses of vaccine with high hemagglutinin (HA) content or the use of adjuvants to achieve the desired neutralizing antibody titers (7)(8)(9)(10)(11). A 2006 H5N1 vaccine trial showed that two doses, each con-taining 90 g of HA, were able to generate microneutralization (MN) titers of Ն1:40 in just half of the subjects (7).…”
mentioning
confidence: 99%
“…A 2006 H5N1 vaccine trial showed that two doses, each con-taining 90 g of HA, were able to generate microneutralization (MN) titers of Ն1:40 in just half of the subjects (7). Similarly, a 2015 H7N9 vaccine trial demonstrated that two AS03-or MF59-adjuvanted doses were required to achieve desired MN titers in the majority of patients (9).…”
mentioning
confidence: 99%